P27 QUIPP Achievement Associated with the Creation of an Accurate Home Oxygen Register and Removal of Inappropriate Short Burst Oxygen Therapy. (19th November 2012) - Fielding, R; Gelder, C; Shakespeare, J
Abstract : Introduction: The Department of Health have identified that the provision of home oxygen is an area where there are significant potentials for both quality improvements and efficiency savings. As part of a programme of work which has included renegotiation of the SHA's home oxygen supply contract, each PCT in the West Midlands has been encouraged to set up a Home Oxygen Assessment and Review service and supported to establish an accurate home oxygen register. Here we report the benefits to one PCT of establishing an accurate home oxygen register and removal of inappropriate short burst oxygen therapy. Methods: A home oxygen register was created by importing billing information into Open Exeter and uploading a list of deducted patients which were checked manually. Patients on short burst oxygen therapy were contacted and clinical need evaluated. Where appropriate these patients were reviewed by the HOS-AR team. The project commenced in July 2011 and was funded by a profit sharing agreement between the local PCT and acute Trust. Results: In 2010/11 Coventry Primary Care Trust (population ∼350, 000) spent approximately £730, 000 on home oxygen therapy (excluding VAT). In July 2011 there were 966 people on the home oxygen register. Removing duplicate entries (67), deceased patients (21) and individuals who had moved to another area (16) reduced the register by 104 with an associated saving of £69588 over a nine month period. Removal of inappropriate short burst oxygen resulted in a monthly saving of approximately £4, 000. Thus an annualised total saving of approximately £150, 000 was achieved which equates to 20% of original spend. Discussion: This demonstrates that significant savings can be achieved rapidly simply by the creation of an accurate home oxygen register and removal of inappropriate short burst oxygen.